2013
DOI: 10.1007/s11906-013-0385-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic and Sympathoexcitatory Actions of NaCl in Hypertension

Abstract: Excess dietary salt intake is a major contributing factor to the pathogenesis of salt-sensitive hypertension. Strong evidence suggests that salt-sensitive hypertension is attributed to renal dysfunction, vascular abnormalities, and activation of the sympathetic nervous system. Indeed, sympathetic nerve transections or interruption of neurotransmission in various brain centers lowers arterial blood pressure (ABP) in many salt-sensitive models. The purpose of this article is to discuss recent evidence that suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 87 publications
1
60
1
Order By: Relevance
“…Despite no detectable change in either plasma sodium or osmolality in the current studies, we speculate minute changes in plasma sodium/osmolality following sodium ingestion sensed by osmoreceptor/sodium-sensitive receptors located in the hypothalamic PVN, the circumventricular organs 4,5 or the renal afferent nerve terminals, 17 trigger the observed alterations in protein expression. Human studies have reported the presence of a single nucleotide polymorphism (SNP) in the human GNAI2 gene is associated with increased hypertension risk by the Millennium Genome Project for Hypertension in Japan 35 and in Caucasian Italians.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Despite no detectable change in either plasma sodium or osmolality in the current studies, we speculate minute changes in plasma sodium/osmolality following sodium ingestion sensed by osmoreceptor/sodium-sensitive receptors located in the hypothalamic PVN, the circumventricular organs 4,5 or the renal afferent nerve terminals, 17 trigger the observed alterations in protein expression. Human studies have reported the presence of a single nucleotide polymorphism (SNP) in the human GNAI2 gene is associated with increased hypertension risk by the Millennium Genome Project for Hypertension in Japan 35 and in Caucasian Italians.…”
Section: Discussioncontrasting
confidence: 71%
“…4,7 The observed genetically conserved endogenous increase in PVN Gαi 2 protein expression in multiple salt-resistant phenotypes, and a failure of this response in the DSS rat, is of high physiological significance because of the pivotal role that the PVN plays in the neural network that influences sympathetic outflow and blood pressure regulation. 18 Our studies 1) implicate sympathetic innervation of the kidney as a critical component in the pathogenesis of salt-sensitive hypertension and, 2) suggest the underlying pathogenesis of salt-sensitive hypertension involves integration of both the central nervous system and the kidneys with communication being regulated by the renal sympathetic nerves via a CNS Gαi 2 protein-gated signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, these findings suggest that TRPV1 and/or TRPV4 channels are not the primary mechanism by which the central nervous system responds to cellular dehydration during hypernatremia or hyperosmolality to increase thirst. hypernatremia; water intake; organum vasculosum of the lamina terminalis; subfornical organ; cellular dehydration THE CENTRAL NERVOUS SYSTEM plays a pivotal role in body fluid homeostasis through its ability to sense changes in osmotic pressure and subsequently alter fluid intake, secretion of antidiuretic hormone, natriuresis, and sympathetic nerve activity (5,19,30,42,45,50). Physiologically, changes in extracellular osmotic pressure are typically the result of changes in the extracellular concentration of Na ϩ and/or Cl Ϫ to produce cellular dehydration.…”
mentioning
confidence: 99%